Non-Standard Employment in Europe - Koch, Max. author. aut Link
XXIV, 246 p.
Keywords: Postwar employment standards are being undermined and 'non-standard' employment is becoming more common. While scholars have pointed to negative consequences of this development, this volume also discusses the evidence for a new and socially inclusive European employment standard.